Posterior pelvic ring fixation: evolution of surgical approaches and evidence-based outcomes for unstable fractures - Zhou, Haiyan; Cheng, Liming (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the clinical outcomes of a novel percutaneous posterior minimally invasive approach for unstable posterior pelvic ring fractures (Tile Type C).MethodsThis retrospective cohort study analyzed 19 consecutive patients treated between 2015 and 2022 at a tertiary trauma center. Inclusion criteria included: 1) adults with Tile C1.1–C1.3 fractures; 2) hemodynamic stability; and 3) minimum 12-month follow-up. Surgical technique featured bilateral 4-cm incisions, subperiosteal tunneling, and anatomically contoured locking plates. Primary outcomes were radiographic union (Matta criteria) and functional recovery (Majeed Pelvic Score).ResultsThe study demonstrated excellent outcomes across all evaluated parameters. All 19 patients achieved bony union within 15.8 ± 4.5 weeks, with 94.7% (18/19) obtaining excellent functional recovery (Majeed score >80). No neurovascular complications or implant failures occurred during the 20-month follow-up. All patients successfully progressed through rehabilitation, achieving full weight-bearing by 12 weeks postoperatively.ConclusionThe percutaneous posterior approach provides effective stabilization for rotationally unstable pelvic fractures with minimal morbidity. While demonstrating advantages in blood loss, operative time, and early mobilization compared to traditional techniques, its applicability remains limited to Tile C1 patterns without vertical instability.